Design and the representability of signs in the world wide web - de Campos, Jorge L.; da Silva, Wallace V. (InfoDesign, 2008)
The present article discusses the following questions and ideas: 1) There is a world wide web characteristic language?; 2) There is on world wide web a own aesthetic?; 3) The dichotomy, divergence or ambiguity on world wide web signals; 4)The literal and symbolic aspects on these imagens. Althought internet be a recent media, questions involving the image are not so new, remonting from the litography (image des-reconstruction) until the semiotic (symbolic information character). The internet itself while ‘new media’ is questioned, while the image discussion is extended to all existent medias (internet included).